Change Management Strategy Through Digital Communication at PT Aruman Aditya - Denyy Aditya (Communicatus: Jurnal Ilmu komunikasi, 2024)
Managerial changes in the era of disruption require rapid adaptation to technological developments, especially in digital communication. PT. Aruman Aditya, a company operating in the developer sector, faces challenges in managing change effectively. This research aims to identify change management strategies through digital communication using an analysis of three key components: effective digital-based communication, continuous training, and technology adoption, as well as a SWOT analysis. The qualitative research collects data through documentation studies, direct observation, and structured interviews. The research results show that effective digital-based communication is vital in conveying the vision of change to all employees. Second, continuous training is essential in ensuring employees can keep up with technological developments. Third, adopting technology through digital communications increases operational efficiency and strengthens inter-divisional collaboration. The results of the SWOT analysis show that PT. Aruman Aditya has strengths in employee competency and technology adoption but faces weaknesses in training costs and resistance to change. The opportunities for developing employee skills are enormous, although threats from technology and intense competition must be faced with the right strategy. In conclusion, PT. Aruman Aditya is in a stable position and is advised to implement progressive strategies to increase the Company's efficiency and competitiveness.